JS09.7.A Reirradiation for recurrent high grade glioma (HGG) patients: results of a single arm prospective phase 2 study. (5th September 2022) - Clerici, E; Navarria, P; Bellu, L; Pessina, F; Simonelli, M; Marini, B; Bianchi, S; Scorsetti, M
Abstract: Background: Standard of care for recurrent high grade glioma (HGG) is missing. Several treatment options have been investigated including re-irradiation (re-RT). Results are promising but provided by retrospective studies. We designed a single arm prospective phase II study aiming to evaluate efficacy, and toxicity of re-irradiation. Material and Methods: Adults patients with good performance status, HGG diagnosis reclassified according to the new 2021 fifth edition WHO CNS classification, an interval time (IT) from previous RT ≥ 6 months were included. Outcome was evaluated by MRI imaging at 1 month, and every 3 months thereafter. Toxicities were evaluated in terms of radionecrosis occurrence, and neurocognitive status. Results: Ninety recurrent HGG patients were treated, 11 oligodendroglioma grade 3, 18 astrocytoma grade 3 and 4, and 61 glioblastoma grade 4. The median age was 54 years, and majority had KPS 90-100. The median IT between first-RT and re-RT was 24 months. Re-surgery has been performed in 56.6%, and chemotherapy in 53.3%. The median follow up time was 64 months; median overall survival (OS) time, 1, 2, 3-year OS rates were 17 months (95%CI 14-19), 66.7%±4.9, 32.6%±5.0, and 22.2 ± 4.7. Prognostic factors impacting on survival were age (p = 0.0154), IT between first RT and re-RT (p = 0.0051), glioma grade (p = 0.0090), and IDH status (p = 0.0001). Radionecrosis grade 2-3 occurred in 9 (10%) patients; neurocognitive functions remained stable until disease progression. Conclusion: Re-RT proved to be a safe and feasible treatment option with low toxicity. Younger patients with grade 3 IDH mutated gliomas, and a longer IT had the better outcome.